2020
DOI: 10.1016/j.immuni.2020.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Multi-omics Analyses Identify Responses of Megakaryocytes, Erythroid Cells, and Plasmablasts as Hallmarks of Severe COVID-19

Abstract: Highlights d SARS-CoV2 infection elicits dynamic changes of circulating cells in the blood d Severe COVID-19 is characterized by increased metabolically active plasmablasts d Elevation of IFN-activated megakaryocytes and erythroid cells in severe COVID-19 d Cell-type-specific expression signatures are associated with a fatal COVID-19 outcome

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
344
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(387 citation statements)
references
References 103 publications
23
344
2
Order By: Relevance
“…In line with those results, we observed attenuated IFN response in the CSF of severe Neuro-COVID and compared with viral encephalitis. Inversely, many studies reported an expansion of plasma cells and plasmablasts ( Bernardes et al., 2020 ; Zhang et al., 2020 ; Zhu et al., 2020 ) that we did not observe in the CSF. Immune alterations may thus be partially shared between compartments and partially compartment specific.…”
Section: Discussioncontrasting
confidence: 80%
“…In line with those results, we observed attenuated IFN response in the CSF of severe Neuro-COVID and compared with viral encephalitis. Inversely, many studies reported an expansion of plasma cells and plasmablasts ( Bernardes et al., 2020 ; Zhang et al., 2020 ; Zhu et al., 2020 ) that we did not observe in the CSF. Immune alterations may thus be partially shared between compartments and partially compartment specific.…”
Section: Discussioncontrasting
confidence: 80%
“…How heme and OXPHOS transcriptional programmes are linked on a molecular level cannot be inferred from our data. Erythroid cell activation has recently been detected in severe COVID-19 (Bernardes et al, 2020) and could also contributes to a heme transcriptional signature. However, the increase in heme metabolism in our cohort correlates strongly with a falling haemoglobin, and reticulocytes ( Figure S7 ) in patients in groups C, D and E are low – suggesting suppression rather than activation of erythropoiesis in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…T cell lymphopenia is a hallmark of acute viral infection, including severe COVID-19 (52) (24) (53) (54), especially within the CD8 T cell compartment (50, 51, 54) and with advanced age (52). This is often accompanied by a concomitant accumulation of memory T cells, particularly in EM and TEMRA subsets (53) (50) (25).…”
Section: Discussionmentioning
confidence: 99%